2015
DOI: 10.1016/j.jbiotec.2015.06.411
|View full text |Cite
|
Sign up to set email alerts
|

Novel high-performance metagenome β-galactosidases for lactose hydrolysis in the dairy industry

Abstract: The industrially utilised β-galactosidases from Kluyveromyces spp. and Aspergillus spp. feature undesirable kinetic properties in praxis, such as an unsatisfactory lactose affinity (KM) and product inhibition (KI) by galactose. In this study, a metagenome library of about 1.3 million clones was investigated with a three-step activity-based screening strategy in order to find new β-galactosidases with more favourable kinetic properties. Six novel metagenome β-galactosidases (M1-M6) were found with an improved l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 32 publications
4
32
0
1
Order By: Relevance
“…meliloti can hydrolyze lactose but not X-Gal, suggestiong that X-Gal was not a good fit with the active sites of those enzymes. The same property of other metagenomic β-galacctosidases has been reported [28]. Here we have highlighted the application of functional metagenomics for mining novel enzymes from soil microbial communities.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…meliloti can hydrolyze lactose but not X-Gal, suggestiong that X-Gal was not a good fit with the active sites of those enzymes. The same property of other metagenomic β-galacctosidases has been reported [28]. Here we have highlighted the application of functional metagenomics for mining novel enzymes from soil microbial communities.…”
Section: Discussionsupporting
confidence: 77%
“…The associated transgalactosylation activity of β-galactosidases can be used to synthesize galactosylated products [24]. Functional screening of metagenomic libraries resulted in discovery of a GH43 enzyme acting on multiple substrates including lactose [25], cold-adapted or thermostable β-galactosidases [2628], GH1/GH2 [2933], two novel β-galactosidases without any similarity to known GHs [7], glycosyltransferase family 4 and β-glycosidase with β-galactosidase activity respectively [34, 35]. …”
Section: Introductionmentioning
confidence: 99%
“…Novas β-galactosidases bem como tecnologias inovadoras ligadas à produção dessa enzima vêm sendo descobertas e estudadas pelos pesquisadores (DUAN et al, 2017;JOSE et al, 2017;LIU et al, 2017;YOU, Chang, et al, 2017;YOU, Zhang, et al, 2017). Erich et al (2015) realizaram uma triagem de 1,3 milhões de clones de metagenoma para descobrir novas β-galactosidases. Seis β-galactosidases de metagenoma foram descobertas e apresentaram melhor desempenho de hidrólise da lactose no leite quando comparado com a β-galactosidase comercial de Kluyveromyces lactis (nome comercial GODO-YNL2, produzida pela Shusei Co, Ltd., Tóquio, Japão).…”
Section: Enzima β-Galactosidaseunclassified
“…It can hydrolyze lactose, mainly being used in food technology for lactose hydrolysis in milk and milk by-products. 6 It can also go through a process called transgalactosylation, taking part in the production of a variety of trans-galactosylation products or prebiotic galacto-oligosaccharides (GOS). It was recently found that these prebiotic products stimulate the growth and establishment of Bifidobacteria in the intestine of human and overcome potentially harmful bacteria, such as species belonging to Clostridia and Bacteriodes in the gut and are now considered as prebiotic.…”
Section: Introductionmentioning
confidence: 99%